A Cloud-Native Serverless Approach for Implementation of Batch Extract-Load Processes in Data Lakes - Bryzgalov, Anton; Stupnikov, Sergey (Data Analytics and Management in Data Intensive Domains, 2021)
The paper presents an approach to deal with batch extract-load processes for cloud data lakes. The approach combines multiple data ingestion techniques, provides advanced failover strategies and adopts cloud-native implementation. The suggested approach. The prototype implementation utilizes Amazon Web Services platform and is based on its serverless features. The approach can be implemented also using other cloud platforms like Google Cloud Platform or Microsoft Azure.